Immediate effects of kinesio-taping and joint mobilisation on shoulder in over-head athletes with glenohumeral internal rotation deficit - Singh, A.; Makhijani, Y.; Sharma, M.; Shenoy, S.; Sandhu, J. (Central European Journal of Sport Sciences and Medicine, 2023)
The purpose of this study was to compare efficacy of kinesio taping (K-taping) and joint mobilization as immediate interventions for treating athletes with glenohumeral internal rotation deficit (GIRD). Thirty-two asymptomatic players were recruited from basketball, volleyball and handball who had a loss of shoulder internal rotation range of motion (IR ROM) of 10 degrees or more on their dominant compared to non-dominant side. They were randomly assigned to 1 of 2 groups: K-taping (n = 16) or joint mobilization (n = 16). Participants in taping group were treated with K-tape for inhibition of external rotators of shoulder and participants in joint mobilization group were treated with grade four Maitland`s mobilization technique for increasing glenohumeral internal rotation. Shoulder internal and external ROM were measured before and after the intervention with a universal goniometer. Both the methods produced significant improvement in IR ROM. The unpaired t-test showed significant change in IR ROM within both the groups (p = 0.003). No significant change was found on comparing both the groups (p = 0.373). There were no significant differences between results of the three sports (p = 0.592). K-taping and joint mobilization both are equally effective in improving the IR ROM in over-head players with GIRD.